Social Media Addiction as a new form of addiction. Is it true? - Hidayati, Hidayati (Journal of Mental Health and Social Rehabilitation, 2024)
Social media is a product of technology that brings significant impact to spread information and connect people around the world and entertainment. As a result, users can access various information easily. In other hand, by using media social excessively lead to dependency that has appears numbers of symptoms that similar with addiction such as impairment in daily functioning (conflict), emerge negative emotions if unable to access social media (withdrawal), having trouble to decrease social media usage (relapse and reinstatement) and social media usage dominates in daily life (salience). However, it is very premature to determine that dependency to social media as a kind of addiction due dependency to social media can be declined without clinical intervention. One of the reasons for declining social media usage is caused by burnout which indirectly pushes the users to keep away from social media. Even though the negative impact from media social usage can not to be ignored due excessive access bring negative consequences to mental health.